Estrategias metodológicas para el docente y su incidencia en el desarrollo del proceso enseñanza - aprendizaje en el aula taller de la carrera de educación parvularia de la Universidad Técnica de Cotopaxi en el sector Eloy Alfaro del cantón Latacunga en la provincia de Cotopaxi durante el periodo lectivo 2011 – 2012 - Álvarez Beltrán, Gladys Yolanda (2013)
The present investigative work is referring about methodological strategies due to reinforce those ones in the teaching learning process because the teachers are trhe fundamental part to improve the strategies to get a significant knowledge and no monotonous classes though this way the students become practical ones and not just theorical from this form mention everyone that the strategically methods appliance into the macro skills the encouragement will be essential in this process the activities ludic, in take part in the shortest ages it will allow them to improve their stages since the first ages in order to reinforce the knowledge taking into a count their independences to get a knowledge in a basic way the students who will be teaching in this way are going to be analytical and reflexives with a lot of moral values for contributing in the society.